THU0305 PREVALENCE AND CLINICAL OUTCOME OF INTERSTITIAL LUNG DISEASE IN ANCA ASSOCIATED VASCULITIS. (2nd June 2020) - Fernandes Serodio, J.; Hernández-Rodríguez, J.; Espígol-Frigolé, G.; Alba, M.; Marco-Hernández, J.; Sánchez, M.; Hernández-González, F.; Sellarés, J.; Cid, M. C.; Prieto-González, S.
Abstract : Background: Lung involvement is frequent in ANCA-associated vasculitis (AAV). Classical lung manifestations consist of capillaritis with lung haemorrhage, inflammatory infiltrates and nodules. Interstitial lung disease (ILD) is increasingly recognized among patients with AAV. However, little is known concerning risk factors and clinical course of these patients. Objectives: The aim of our study was to characterize the prevalence and clinical course of ILD in patients with AAV. Methods: We have performed a clinical retrospective single-centre observational analysis (1990-2019) of all patients with the diagnosis of microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) diagnosed according to 2018 Draft Classification Criteria for GPA and MPA 1 . Demographic, clinical and immunologic data were reviewed. Radiologic pattern of ILD were assessed by high-resolution-CT. Main outcome evaluated was overall-all survival. Results: The study population consisted of 123 patients, 56% female, aged 59.3±18.2 years old at the time of diagnosis. Clinical diagnosis was of MPA in 54% of patients and GPA in 46%. While 108 (88%) ANCA positive patients had PR3 (n=25) or MPO (n=83), 15 (12%) patients had negative or atypical ANCA. Any lung involvement was present in 82 (71%) and ILD was identified in 24 (20%) of all patients. ILD pattern was of usual interstitial pneumonia (UIP) in 12 patients, non-specified interstitial pneumonia (NSIP) in 9 and chronic organizing pneumonia (OP) in 3. There was an association between the presence of ILD and ANCA specificity: MPO were present in 100% of patients with UIP and in 75% of patients with NSIP/OP (p=0.017). Bronchiectasis were more prevalent among patients with ILD (19/24; p<0.001). During the median follow-up time period of 68 (23-126) months, mortality was of 42% among patients with ILD-AAV compared with 11% in no ILD-AAV (log-rank p=0.0001). On the multivariate Cox regression model, ILD was an independent predictor of mortality HR 2.95 (95%CI 1.09-7.96; p=0.033). Conclusion: ILD is a frequent manifestation of MPA and GPA patients. The presence of ILD, particularly UIP, is associated with ANCA-MPO and is a predictor of mortality. Therefore, a better management of fibrotic lung involvement in AAV is warranted. References: [1]Robson JC, Grayson PC, Ponte C, et al. Draft classification criteria for the ANCA associated vasculitides. Ann Rheum Dis 2018;77 (suppl 2):60-1. Disclosure of Interests: João Fernandes Serodio: None declared, José Hernández-Rodríguez: None declared, Georgina Espígol-Frigolé: None declared, Marco Alba: None declared, Javier Marco-Hernández: None declared, Marcelo Sánchez: None declared, Fernanda Hernández-González: None declared, Jacobo Sellarés: None declared, Maria C. Cid Grant/research support from: Kiniksa Pharmaceuticals, Consultant of: Janssen, Abbvie, Roche, GSK, Speakers bureau: Vifor, Sergio Prieto-González: None declared